PENGARUH PERNIKAHAN SEDARAH DALAM TRADISI ANA TUYA DAN ANA MAMU (ANAK OM DAN ANAK TANTE) TERHADAP KETURUNAN DI DESA WATU PUDA KECAMATAN UMALULU KABUPATEN SUMBA TIMUR - Riwa, Milintari T R; Pello, Helsiana F; Kaesmetan, Rini M (Petitum Law Journal, 2026)
This research explores the cultural tradition of consanguineous marriage in the Ana Tuya and Ana Mamu tradition in Watu Puda Village, East Sumba, where marriage between maternal uncle’s daughter and paternal aunt’s son is still practiced. Using an empirical legal approach with qualitative methods, this study investigates why the tradition continues and examines its effects on offspring. The findings reveal that the tradition persists due to cultural preservation, the influence of Marapu customary law, and family expectations. However, the consequences include a heightened risk of genetic disorders, psychological pressure, and, in some cases, birth defects and mental developmental delays in children. The study underscores the need for education, genetic counseling, and dialogue between tradition and public health to reduce the harmful impacts on future generations.